2022
DOI: 10.3324/haematol.2021.280292
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immunosuppressive role of myeloid-derived suppressor cells in acquired aplastic anemia

Abstract: Myeloid-derived suppressor cells (MDSCs) are a group of heterogeneous immature myeloid cells and display immunosuppressive function. In this study, MDSCs populations were evaluated in acquired aplastic anemia (AA) (n=65) in which aberrant immune mechanisms contributed to bone marrow destruction. Our data demonstrate that both the proportion and immunosuppressive function of MDSCs are impaired in AA patients. Decreased percentage of MDSCs, especially monocytic-MDSCs, in the blood of AA patients (n=15) is positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Feng et al have recently reported that PMN-MDSCs potently suppress T cell-mediated BM failure using a mouse model of immune-mediated aplastic anemia [82]. Conceptionally, these data are similar to those of Dong et al who reported that patients with severe immune-mediated aplastic anemia have fewer circulating M-MDSCs that possess impaired immunosuppressive activity [83].…”
Section: Potential Mechanism Involved In Suppressing Disease In Outbr...supporting
confidence: 74%
“…Feng et al have recently reported that PMN-MDSCs potently suppress T cell-mediated BM failure using a mouse model of immune-mediated aplastic anemia [82]. Conceptionally, these data are similar to those of Dong et al who reported that patients with severe immune-mediated aplastic anemia have fewer circulating M-MDSCs that possess impaired immunosuppressive activity [83].…”
Section: Potential Mechanism Involved In Suppressing Disease In Outbr...supporting
confidence: 74%
“…S2). Previous research has pointed to a signi cant decrease in MDSC proportions in AA, linked to a noticeable reduction in immunosuppressive capabilities [20]. Employing ow cytometry-based sorting, we isolated MDSCs from both HDs and AA patients for Smart-seq analysis.…”
Section: Nk Cells With a Less Functional Cd56 Dim Molecular Signature...mentioning
confidence: 99%
“…CAA primarily results from genetic mutations, with the diagnosis of congenital bone marrow failure relying mainly on NGS sequencing. In AA, MDSCs exert immunosuppressive effects, leading to a signi cant decrease in their components [20]. We further evaluated the percentage of HLA-DR − CD11b + CD33 + MDSCs in AA and CAA, revealing a marginal decrease in MDSCs in AA compared to the HDs.…”
Section: Nk Cells With a Less Functional Cd56 Dim Molecular Signature...mentioning
confidence: 99%